Bagaimana Gamers Berperilaku Trash-Talk? - Aprillia Setyaning Normalisa Putri; Yeni Rahmawati; Panji Putra Ariyanto (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2021)
Playing online games together (mabar) produces a form of aggressive behavior, namely trashtalk. Trashtalk is a form of verbal communication that is carried out consciously or intentionally by individuals for positive and negative personal reasons.Trashtalk became anxious because of its high intensity and contrary to the socio-religious morals of Muslim students. This research uses a case study approach with the initial stages in the form of a survey exploring the trashtalk phenomenon, selecting the main sources, in-depth interviews, observation and member checking as a data validation step. This study found that the causes of trashtalk consist of internal and external factors. More forms of behavior are displayed with cynical, sexist and intimidating swear words. The impact is personal satisfaction and becomes an innate behavior when communicating outside of playing games. The unique thing obtained is that the trashtalk perpetrators feel guilty and make istigfar as compensation for these feelings.